Anti-precipitation coating and polyester film

By using specific design anti-precipitation coatings on BOPET films, including high solid hydroxyl resins, isocyanate-based curing agents and microparticles, a dense crosslinking network structure is formed, which solves the problem that existing coatings are easily destroyed in high temperature and high humidity environments, and significantly improves the anti-precipitation performance and optical performance.

CN119799090APending Publication Date: 2025-04-11ZHANGJIAGANG KANGDE XIN OPTRONICS MATERIAL

Patent Information

Application Number
CN202411922030.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing water-based anti-precipitation coatings are easily damaged in high temperature and high humidity environments, resulting in a decrease or loss of anti-precipitation performance, affecting the optical performance and application characteristics of BOPET films.

Method used

Anti-precipitation coatings including hydroxy resin and curing agent are used. The solid hydroxyl value of the hydroxy resin is 60-120 mgKOH/g, the average mass molecular weight is 20,000-150,000, and the glass transition temperature is between 60℃-110℃. Combined with isocyanate curing agent and microparticles, a dense crosslinking network structure is formed to improve the anti-precipitation and adhesive properties of the coating.

Benefits of technology

It significantly improves the coating's anti-precipitation performance, thermal stability and adhesion, ensures that the coating maintains stability and transparency in high temperature environments, maintains the optical properties of BOPET films, and enhances the coating's hardness, wear resistance and UV resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to an anti-precipitation coating and a polyester film, and relates to the technical field of optics, the anti-precipitation coating comprises hydroxyl resin and a curing agent; the solid hydroxyl value of the hydroxyl resin is 60 to 120 mgKOH / g, the mass-average molecular weight of the hydroxyl resin is 20,000 to 150,000, and the glass transition temperature of the hydroxyl resin is 60 to 110 DEG C. By reasonably designing the molecular weight, the glass transition temperature, the solid hydroxyl value and other parameters of the hydroxyl resin and matching with the curing agent, the precipitation resistance, the high temperature resistance and the thermal stability of the coating and the bonding performance of the coating with a subsequently processed coating are optimized; the coating not only can effectively inhibit the precipitation phenomenon and ensure the stability of the coating, but also can maintain the optical performance of the BOPET film, so that the BOPET film has excellent durability, stability and aesthetic property in practical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of optical technology, and in particular to an anti-precipitation coating and a polyester film. Background Art

[0002] Biaxially oriented polyester film (BOPET) is a film made by longitudinally and transversely stretching polyethylene terephthalate (PET) material. It has excellent optical properties, mechanical properties, heat resistance and high insulation, and is therefore widely used in the field of optoelectronic products. However, in order to meet the diverse functional requirements of BOPET film in different applications, the film often needs to be deeply processed. In this process, due to the diversity of processing conditions and usage conditions, oligomers may precipitate and crystallize on the surface of the film. The precipitation of these low molecular weight substances will cause the surface of the film to turn white, reduce visibility, and thus affect subsequent processing, and may even contaminate internal components in the processing process, ultimately affecting the optical properties and application characteristics of the film.

[0003] At present, water-based anti-precipitation coatings are widely used in the market to solve this problem. These coatings are usually applied during the film manufacturing process to prevent the precipitation of oligomers. However, due to the limited degree of curing of water-based coatings and the thin coatings, the coatings often contain a large number of hydrophilic groups, which may cause the coatings to be destroyed in high temperature and high humidity environments, resulting in a decrease in or complete loss of anti-precipitation performance, resulting in a higher haze or precipitation of low-molecular substances in the processed BOPET film, which cannot meet some high-demand applications.

[0004] In order to solve the above problems, patent CN107641454A discloses a solution for solvent-based anti-precipitation primer, that is, a layer of UV glue with a thickness of 1-5 microns is coated on the surface of the PET film, and the water contact angle of the coating is greater than 100°. The anti-precipitation coating prepared by this method is thicker and needs to be cured by UV, but due to the high cost of UV coating and the poor adhesion between it and the subsequent processing coating, it will also cause powdering during the subsequent die-cutting process, thereby limiting its application effect and economy. Summary of the invention

[0005] In order to improve the anti-precipitation performance of the anti-precipitation coating and its bonding effect with the subsequent processing coating, while ensuring the optical properties of the BOPET film, the present application provides an anti-precipitation coating and a polyester film.

[0006] The present application provides an anti-precipitation coating and polyester film using the following technical solutions: An anti-precipitation coating comprises a hydroxy resin and a curing agent; the solid hydroxy value of the hydroxy resin is 60-120 mgKOH / g, the mass average molecular weight of the hydroxy resin is 20,000-150,000, and the glass transition temperature of the hydroxy resin is 60-110°C.

[0007] By adopting the above technical scheme, the present application selects a hydroxyl resin with a solid hydroxyl value of 60-120 mgKOH / g. A higher solid hydroxyl value means that there are more -OH groups on the resin molecules. These groups can form a cross-linking reaction with the curing agent during the curing process, provide more reaction sites, and generate a dense cross-linked network structure, thereby improving the low-resistance barrier performance of the coating, reducing the precipitation or migration of low-molecular substances, and effectively preventing the influence of precipitates or low-molecular substances in the material on the coating performance, and improving the anti-precipitation performance of the coating; selecting a hydroxyl resin with a molecular weight between 20,000 and 150,000 can provide a reasonable molecular chain length in the coating, which can not only ensure that the coating has sufficient mechanical strength, but also promote the cross-linking effect between the resin molecules, so that the coating surface has good adhesion, thereby improving the adhesion between the coating and the subsequent processing coating; The glass transition temperature (Tg) of hydroxyl resin is between 60℃ and 110℃, which can ensure the stability of the coating within the normal use temperature range. The higher Tg makes the coating less likely to soften or deform during thermal processing, effectively ensuring the transparency and flatness of the coating, thereby maintaining the optical properties of the BOPET film. The coating optimizes the coating's anti-precipitation properties, high temperature resistance, thermal stability and adhesion properties with subsequent processed coatings by rationally designing parameters such as the molecular weight, glass transition temperature and solid hydroxyl value of the hydroxyl resin. The coating can not only effectively inhibit precipitation and ensure coating stability, but also maintain the optical properties of the BOPET film, giving it excellent durability, stability and aesthetics in practical applications.

[0008] In a specific embodiment, the hydroxy resin is a hydroxy acrylic resin.

[0009] By adopting the above technical scheme, hydroxyl acrylic resin is selected as the hydroxyl resin. Hydroxylated acrylic resin has abundant hydroxyl (—OH) groups, which can react chemically with the curing agent to form a denser cross-linked network during the curing process, thereby further improving the anti-precipitation performance of the coating. Hydroxylated acrylic resin has excellent reactivity and can form good chemical bonding or physical adsorption with subsequent coatings during the curing process, thereby further improving the adhesion with subsequent coatings. In addition, hydroxylated acrylic resin has good optical properties, and its transparency, smoothness, and uniformity of the coating can well meet the optical requirements of BOPET film.

[0010] In a specific embodiment, the curing agent is an epoxy curing agent or an isocyanate curing agent.

[0011] By adopting the above technical solutions, epoxy curing agents can provide excellent cross-linking, chemical resistance, thermal stability and adhesion, and are suitable for applications requiring high mechanical strength, corrosion resistance and long-term stability; while isocyanate curing agents have faster curing speed, good elasticity, toughness and weather resistance, and are suitable for applications requiring wear resistance, UV resistance and environmental protection requirements.

[0012] In a specific embodiment, the molar equivalent ratio NCO / OH of the isocyanate group of the isocyanate curing agent to the hydroxyl group of the hydroxy acrylic resin is 0.7-1.2.

[0013] By adopting the above technical scheme, the rate of the curing reaction and the cross-linking density can be controlled by adjusting the molar equivalent ratio of isocyanate groups to hydroxyl groups, so that the bonding and anti-precipitation effects can be adjusted as needed. In the range of NCO / OH ratio of 0.7-1.2, the curing reaction can avoid both excessive cross-linking (resulting in increased brittleness) and insufficient cross-linking (resulting in insufficient strength), thereby obtaining balanced performance; when the NCO / OH ratio is close to 0.7, the reaction is milder and can provide better flexibility; and when it is close to 1.2, the cross-linking density is higher, which can provide stronger rigidity and impact resistance.

[0014] In a specific embodiment, the anti-separation coating further comprises microparticles, and the microparticles are selected from one or a combination of silica particles, polyacrylate particles, and polystyrene particles.

[0015] By adopting the above technical scheme, silica particles, polyacrylate particles and polystyrene particles are added to the anti-precipitation coating, so as to improve the surface smoothness and performance of the coating; the addition of microparticles improves the smoothness, hardness, wear resistance, scratch resistance and UV resistance of the coating through its physical properties, dispersion effect and combination with the coating matrix, and improves the comprehensive performance of the coating, so that the coating not only has excellent appearance effect, but also has good physical durability and chemical stability; in addition, the addition of microparticles also helps to optimize the leveling of the coating, improve the processability of the coating and production efficiency, and is an effective means to improve the quality of the coating.

[0016] In a specific embodiment, the particle size D50 of the microparticles is between 0.1 μm and 1.5 μm.

[0017] By adopting the above technical solution, the average particle size of the microparticles is smaller, with better dispersibility and surface coverage. The microparticles can be evenly distributed in the coating, thereby improving the surface smoothness and touch of the coating while reducing the roughness; and the tiny microparticles can better fill the microscopic gaps in the coating and enhance its mechanical strength and durability.

[0018] In a specific embodiment, the amount of the microparticles added is 0%-10% of the solid content of the hydroxyl resin.

[0019] By adopting the above technical solution and controlling the amount of microparticles added within the range of 0%-10% of the solid content of the hydroxyl resin, it is possible to improve the coating performance while avoiding the adverse effects of excessive microparticles on the workability and flexibility of the coating, thereby improving the surface smoothness, wear resistance, scratch resistance, adhesion and flexibility of the coating.

[0020] A polyester film comprises a substrate layer and an anti-precipitation coating arranged on at least one side of the substrate layer, wherein the anti-precipitation coating is obtained by curing the anti-precipitation coating described above.

[0021] By adopting the above technical scheme, the coating formed by the anti-precipitation coating can improve the durability and anti-aging performance of the polyester film; the anti-precipitation coating can ensure the long-term stability of the coating on the surface of the substrate layer, avoid the generation of uneven precipitates or surface defects on the surface, thereby greatly improving the durability and service life of the polyester film; the anti-precipitation coating can form a coating with good adhesion to the polyester film substrate layer, and the close combination of the coating and the substrate can not only effectively avoid precipitation, but also enhance the stability of the film under different environmental conditions. Under high humidity, high temperature or changing environmental conditions, the anti-precipitation coating can maintain the integrity of the polyester film and avoid performance degradation caused by environmental factors; and the anti-precipitation coating prepared using the anti-precipitation coating of the present application has good transparency and optical effect, can ensure the transmittance and smoothness of the polyester film, improve the optical performance, and can meet the requirements of applications (such as optical devices, display screens, etc.) with high transparency and optical precision.

[0022] In a specific embodiment, the anti-precipitation coating has a thickness of 0.3 μm-0.6 μm.

[0023] By adopting the above technical solution and using the design of an anti-precipitation coating with a thickness of 0.3μm-0.6μm, moderate protection performance can be provided, which not only ensures the anti-precipitation function of the polyester film, but also does not have a negative impact on other properties of the polyester film (such as transparency, flexibility, optical effects, etc.).

[0024] In a specific embodiment, the polyester film has a film haze of less than 1.0%.

[0025] By adopting the above-mentioned technical scheme, the polyester film using the anti-precipitation coating of the present application can ensure clarity while ensuring the anti-precipitation effect. The polyester film with a film haze of less than 1.0% has extremely high transparency and clarity, and is suitable for application fields that require transparent and clear effects. It can provide excellent visual effects and optical properties, and improve the product appearance quality and functional performance.

[0026] In summary, the present application includes at least one of the following beneficial technical effects: by reasonably designing the molecular weight, glass transition temperature, solid hydroxyl value and other parameters of the hydroxy acrylic resin, combined with isocyanate curing agents and an appropriate amount of microparticles, the anti-precipitation, thermal stability and adhesion of the coating are effectively improved, ensuring that the coating maintains stability and transparency in a high temperature environment, and maintaining the optical properties of the BOPET film; the hardness, wear resistance, scratch resistance and UV resistance of the coating are enhanced, and the rheology, dispersibility and processing performance of the coating are optimized, so that the coating has excellent durability, stability and aesthetics. The coating can not only effectively inhibit precipitation, but also ensure the stability of subsequent coatings and excellent performance in long-term use; The coating formed by the anti-precipitation coating can improve the durability and anti-aging performance of the polyester film; the anti-precipitation coating can form a coating with good adhesion to the polyester film substrate layer. The close combination of the coating and the substrate can not only effectively avoid precipitation, but also enhance the stability of the film under different environmental conditions. Under high humidity, high temperature or changing environmental conditions, the anti-precipitation coating can maintain the integrity of the polyester film and avoid performance degradation due to environmental factors; and the anti-precipitation coating prepared using the anti-precipitation coating of the present application has good transparency and optical effect, can ensure the transmittance and smoothness of the polyester film, improve the optical properties, and can meet the applications requiring high transparency and optical precision. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the structure of the polyester film in the embodiment of the present application.

[0028] Explanation of reference numerals: 1. anti-precipitation coating; 2. substrate layer. DETAILED DESCRIPTION

[0029] The following is combined with Figure 1 This application is described in further detail.

[0030] Embodiment 1 The present application embodiment discloses an anti-precipitation coating, and the anti-precipitation coating includes but is not limited to being applied to biaxially oriented polyester film (BOPET); The anti-precipitation coating includes hydroxyl resin and curing agent; the solid hydroxyl value of hydroxyl resin is 60-120mgKOH / g. A higher solid hydroxyl value means that there are more hydroxyl (—OH) groups on the resin molecules. These groups can form a cross-linking reaction with the curing agent during the curing process, provide more reaction sites, and generate a dense cross-linked network structure, thereby improving the low-resistance blocking performance (anti-precipitation performance) of the coating, reducing the precipitation or migration of low-molecular substances, effectively preventing the influence of precipitates or low-molecular substances in the material on the coating performance, and improving the anti-precipitation performance of the coating; The mass average molecular weight of the hydroxy resin is 20,000-150,000. Compared with low molecular weight polymers, the molecular chains of the hydroxy resin under this condition become longer and their interactions are enhanced, and the polymer chains are more tightly entangled, requiring more energy to overcome these effects to make the molecular chains move or deform, thereby showing better heat resistance, which can not only ensure that the coating has sufficient mechanical strength, but also promote the cross-linking effect between the resin molecules, so that the coating surface has good adhesion, thereby improving the adhesion between the coating and the subsequent processing coating; The glass transition temperature (Tg) of hydroxyl resin is between 60℃ and 110℃. Compared with resins with low glass transition temperatures, the temperature at which the material softens and begins to deform is higher. The higher Tg makes the coating less likely to soften or deform during thermal processing, and the original shape and performance of the material can be maintained at higher temperatures, thereby ensuring that the coating remains stable within the normal operating temperature range, effectively ensuring the transparency and flatness of the coating, and thus maintaining the optical properties of the BOPET film. By rationally designing parameters such as the molecular weight, glass transition temperature and solid hydroxyl value of the hydroxyl resin, the anti-precipitation coating's anti-precipitation properties, high temperature resistance, thermal stability and adhesion properties with subsequent processed coatings are optimized; the anti-precipitation coating can not only effectively inhibit the precipitation phenomenon and ensure the stability of subsequent coatings, but also maintain the optical properties of the BOPET film, giving it excellent durability, stability and aesthetics in practical applications.

[0031] The hydroxy resin is a hydroxy acrylic resin; hydroxy acrylic resin is selected as the hydroxy resin, and the hydroxy acrylic resin has abundant hydroxyl (—OH) groups, which can react chemically with the curing agent to form a denser cross-linking network during the curing process, thereby further improving the anti-precipitation performance of the coating; the hydroxy acrylic resin has excellent reactivity, and can form good chemical bonding or physical adsorption with subsequent coatings during the curing process, thereby further improving the adhesion with subsequent coatings; and the hydroxy acrylic resin has good optical properties, and its transparency, smoothness, and uniformity of the coating can well meet the optical requirements of the BOPET film.

[0032] The curing agent is an epoxy curing agent or an isocyanate curing agent. In this embodiment, the epoxy curing agent includes but is not limited to aliphatic amine curing agents, aromatic amine curing agents, anhydride curing agents, and polyamide curing agents. The epoxy curing agent can provide excellent cross-linking, chemical resistance, thermal stability and adhesion, and is suitable for applications requiring high mechanical strength, corrosion resistance and long-term stability. In this embodiment, the isocyanate curing agent includes but is not limited to diphenylmethane diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, and isophorone diisocyanate; the isocyanate curing agent has a faster curing speed, good elasticity, toughness and weather resistance, and is suitable for applications requiring wear resistance, UV resistance and environmental protection requirements; In this embodiment, preferably, the curing agent is an isocyanate curing agent; the molar equivalent ratio NCO / OH of the isocyanate group of the isocyanate curing agent to the hydroxyl group of the hydroxy acrylic resin is 0.7-1.2. In this embodiment, preferably, NCO / OH is 0.9-1.05; By adjusting the molar equivalent NCO / OH ratio of isocyanate groups to hydroxyl groups, the rate of the curing reaction and the crosslinking density can be controlled, so that the bonding and anti-precipitation effects can be adjusted as needed; when the NCO / OH ratio is too low, the crosslinking density is insufficient, resulting in a soft cured layer with poor chemical resistance and wear resistance; when the ratio is too high, it may lead to excessive crosslinking, and the coating becomes brittle and hard, affecting flexibility and impact resistance; therefore, a ratio of 0.9-1.05 can achieve a good balance in performance, avoiding both excessive crosslinking (increasing brittleness) and insufficient crosslinking (inadequate strength), thereby obtaining balanced performance; when the NCO / OH ratio is close to 0.9, the reaction is milder and can provide better flexibility; when it is close to 1.05, the crosslinking density is higher, which can provide stronger rigidity and impact resistance.

[0033] The anti-precipitation coating also includes microparticles, which are selected from one or a combination of silica particles, polyacrylate particles, and polystyrene particles; in this embodiment, the silica particles can increase the stability of the coating through physical effects (such as interactions between particles) to prevent the components from precipitating or settling, and their small particle size and high surface area can help improve the suspension stability of the coating; the polyacrylate particles have strong dispersibility and hydrophilicity, which can effectively prevent other components in the coating from agglomerating or precipitating. By forming a stable dispersion system, the polyacrylate particles can improve the anti-precipitation property of the coating and ensure that the coating remains uniform and stable during storage; the addition of polystyrene particles helps to improve the dispersibility and rheology of the coating, and prevents uneven distribution or precipitation of the coating during storage or use. In addition, the hydrophobic characteristics of the polystyrene particles can reduce the influence of moisture on the coating system and enhance the anti-settling and anti-precipitation properties of the coating; The addition of microparticles improves the smoothness, hardness, wear resistance, scratch resistance and UV resistance of the coating through its physical properties, dispersion effect and combination with the coating matrix, and enhances the overall performance of the coating, so that the coating not only has excellent appearance, but also has good physical durability and chemical stability; in addition, the addition of microparticles also helps to optimize the leveling of the coating, improve the processability and production efficiency of the coating, and is an effective means to improve the quality of the coating.

[0034] The particle size D50 of the microparticles is between 0.1 μm and 1.5 μm. In the present embodiment, preferably, the particle size D50 of the microparticles is between 1.0 μm and below. The average particle size of the microparticles is small, which can provide a larger specific surface area and increase the contact area between the microparticles and the coating matrix, so that the microparticles can be more effectively dispersed in the coating system, preventing the sedimentation and precipitation of other components and ensuring the long-term stability of the coating. In addition, microparticles with smaller particle sizes can improve the rheological properties of the coating and adjust the viscosity of the coating, so that it has better fluidity and operability during use and avoids uneven coating or sagging. It can also enhance the adhesion of the coating to subsequent coatings, promote the adhesion of the coating by providing more contact points, and prevent the coating from peeling or falling off.

[0035] The amount of microparticles added is 0%-10% of the solid content of the hydroxyl resin; the addition of microparticles helps to improve the hardness, wear resistance and scratch resistance of the coating. The right amount of microparticles can form a denser structure on the surface of the coating, thereby improving the durability of the coating, especially when the addition amount is high (close to 10%); the addition amount range of 0%-10% can avoid excessive hardening, so that the coating maintains a certain strength without losing appropriate toughness, thereby improving the adhesion and surface gloss of the coating, and improving the durability and construction performance of the coating.

[0036] The anti-precipitation coating disclosed in this embodiment effectively improves the anti-precipitation, thermal stability and adhesion of the coating by reasonably designing the molecular weight, glass transition temperature, solid hydroxyl value and other parameters of the hydroxy acrylic resin, combining isocyanate curing agent, and an appropriate amount of microparticles (such as silica, polyacrylate or polystyrene particles), ensuring that the coating maintains stability and transparency in a high temperature environment and maintains the optical properties of the BOPET film; enhances the hardness, wear resistance, scratch resistance and UV resistance of the coating, optimizes the rheology, dispersibility and processing performance of the coating, and makes the coating have excellent durability, stability and aesthetics. The coating can not only effectively inhibit precipitation, but also ensure the stability of subsequent coatings and excellent performance in long-term use.

[0037] Embodiment 2 Reference Figure 1This embodiment discloses a polyester film. In this embodiment, the polyester film is a biaxially stretched polyester film, which is a product obtained by biaxially (longitudinally and transversely) stretching polyethylene terephthalate (PET); The polyester film includes a substrate layer 2 and an anti-precipitation coating 1 provided on at least one side of the substrate layer 2. In this embodiment, the material of the substrate layer 2 includes but is not limited to polyethylene terephthalate (PET), and the anti-precipitation coating 1 is obtained by curing the anti-precipitation coating described in the first embodiment; In this embodiment, preferably, an anti-precipitation coating 1 is provided on both sides of the substrate layer 2; by coating the anti-precipitation coating 1 on both sides of the substrate layer 2, the precipitation phenomenon of the coating components can be effectively prevented. Since the polyester film has the anti-precipitation coating 1 on both sides, the double coating design further improves the stability of the polyester film, so that the polyester film can maintain good chemical stability under different environmental conditions, avoiding performance degradation or appearance damage caused by precipitation.

[0038] The thickness of the anti-precipitation coating 1 is 0.3 μm-0.6 μm, which can provide appropriate protection performance, ensure the anti-precipitation function of the polyester film, and will not have a negative impact on other properties of the polyester film (such as transparency, flexibility, optical effect, etc.).

[0039] In this embodiment, the film haze of the polyester film is below 1.0%; the polyester film using the anti-precipitation coating of the present application can ensure clarity while ensuring the anti-precipitation effect. The polyester film with a film haze of less than 1.0% has extremely high transparency and clarity, is suitable for application fields that require transparent and clear effects, can provide excellent visual effects and optical properties, and improve product appearance quality and functional performance.

[0040] The polyester film of the present application, through the coating formed by the anti-precipitation coating, can improve the durability and anti-aging performance of the polyester film; the anti-precipitation coating can ensure the long-term stability of the coating on the surface of the substrate layer 2, avoid the generation of uneven precipitates or surface defects on the surface, thereby greatly improving the durability and service life of the polyester film; the anti-precipitation coating can form a coating with good adhesion to the polyester film substrate layer 2, and the close combination of the coating and the substrate can not only effectively avoid precipitation, but also enhance the stability of the film under different environmental conditions. Under high humidity, high temperature or changing environmental conditions, the anti-precipitation coating 1 can maintain the integrity of the polyester film and avoid performance degradation caused by environmental factors; and the anti-precipitation coating 1 prepared using the anti-precipitation coating of the present application has good transparency and optical effect, can ensure the transmittance and smoothness of the polyester film, improve the optical performance, and can meet the applications requiring high transparency and optical precision (such as optical devices, display screens, etc.).

[0041] In this embodiment, the preparation process of the polyester film of the present application includes the following steps: 1. Preparation of polyester film substrate layer 2 (1) Raw material selection: First, polyethylene terephthalate (PET) is selected as the substrate. PET is a common thermoplastic polyester with good mechanical strength, chemical stability and transparency, and is widely used in film manufacturing; (2) Melt extrusion: After the PET resin is heated to a molten state, melt extrusion molding is performed. The molten PET is extruded into a film-like substrate through a mold. This process usually forms the initial shape and thickness of the film.

[0042] (3) Biaxial stretching: Next, the extruded PET film is biaxially stretched in the longitudinal and transverse directions. The longitudinal stretching orients the molecular chains of the film along the machine direction, while the transverse stretching orients the molecular chains in the vertical direction. This process helps to improve the mechanical properties, tensile strength and transparency of the film. Longitudinal stretching: usually carried out at a temperature of 150-220°C, the film increases in length and decreases in thickness during the stretching process; Transverse stretching: After longitudinal stretching, the film will be further stretched in the transverse direction, usually by heated rollers or air flow. This process enhances the molecular orientation of the film and further improves the mechanical and optical properties of the film.

[0043] 2. Preparation of anti-precipitation coating 1 (1) Selection and preparation of anti-precipitation coating The anti-precipitation coating includes: hydroxy acrylic resin (as a base material); isocyanate curing agent (reacts with the hydroxy resin for cross-linking); microparticles (improve the performance of the coating and enhance the anti-precipitation ability); Selection of hydroxyl acrylic resin: solid hydroxyl value 60-120mgKOH / g, to ensure that the resin has enough hydroxyl groups to react with isocyanate curing agent; molecular weight 20,000-150,000, to ensure the mechanical strength and flexibility of the coating; glass transition temperature (Tg): in the range of 60-110℃, to ensure the stability of the coating at room temperature; Isocyanate curing agent The molar equivalent ratio of isocyanate group to hydroxyl group is NCO / OH=0.7-1.2, which ensures the efficient curing reaction and avoids the side effects of excessive isocyanate; Curing agent dosage: determined by the molar ratio with hydroxy resin.

[0044] Microparticles Type of microparticles: selected from one or a combination of silica particles, polyacrylate particles, and polystyrene particles, these microparticles can increase the wear resistance, scratch resistance and structural stability of the coating; The amount of microparticles added: The amount of microparticles added is 0%-10% of the solid content of the hydroxy resin. For example, if 30g of hydroxy resin (solid content is 50%) is used, the amount of microparticles added is 0-1.5g.

[0045] (2) Preparation method of anti-precipitation coating Dissolve the hydroxyl resin: Add the hydroxyl acrylic resin to an appropriate amount of solvent (such as ethyl acetate or butanone), and heat to 60°C-70°C under stirring to ensure that the resin is completely dissolved.

[0046] Adding microparticles: Add microparticles (such as silica particles) to the solution and continue stirring to ensure that the microparticles are evenly dispersed. Ultrasonic or high shear stirring equipment can be used for dispersion treatment; Add curing agent: add isocyanate curing agent to the above mixture, preferably, ensure that the NCO / OH ratio is between 0.9-1.05, and continue stirring for 10-20 minutes to allow the curing agent to fully react with the resin; Adjust viscosity: Add appropriate amount of solvent to adjust the viscosity of the coating as needed. The viscosity of the coating should be suitable for the coating process (such as scraper coating, spray coating, roller coating, etc.); Filtration and packaging: Filter the paint through a filter (such as a 200-mesh filter) to remove large particles of impurities to ensure the uniformity and quality of the paint, and then package the paint in a sealed container to prevent solvent volatilization.

[0047] (3) Coating and curing of anti-precipitation coating 1 Coating: Coat the anti-precipitation coating on both sides of the PET film. The coating thickness is controlled within the range of 0.3μm-0.6μm. The coating can be carried out by scraping, rolling or spraying to ensure uniform coating. Curing: The polyester film coated with the anti-precipitation coating is sent to an oven for curing at a temperature of 100°C-150°C for 10-20 minutes to ensure that a strong chemical bond is formed between the coating and the substrate layer 2. This process can not only fully cross-link the coating, but also enhance the anti-precipitation performance of the film; Cooling and cutting: After the solidified film is naturally cooled to room temperature, it is cut to size to obtain the final polyester film product that meets the requirements.

[0048] In this embodiment, in order to more clearly illustrate the technical solution of the present invention, hydroxyl acrylic resins with different molecular weights, glass transition temperatures, and solid hydroxyl value parameters are designed and selected, different curing agents are designed and selected, isocyanate type curing agents and hydroxyl acrylic resins with different NCO / OH (0.7-1.2) are designed and selected, different amounts of microparticles are designed to be added, and different thicknesses of anti-precipitation coatings 1 are designed to be formed on the substrate layer 2; the effects of the anti-precipitation coatings 1 prepared under different conditions on the performance of the polyester film are tested and compared, and the following is explained in conjunction with specific implementation cases: Example 1 An anti-precipitation coating is prepared by using 100 parts of hydroxy acrylic resin (solid content 50%), with a glass transition temperature of 60°C, a mass average molecular weight of 100,000, and a solid hydroxyl value of 120 mgKOH / g; 15 parts of isocyanate curing agent (Desmodur L-75), with an NCO / OH ratio of 0.7; the coating is applied on both sides of a 50 μm PET substrate layer 2 (KFDN-50SG5P) to form an anti-precipitation coating 1, with a single-side dry thickness of 0.5 μm, to prepare a polyester film; and the coating is tested after aging at 50°C for 24 hours.

[0049] Example 2 An anti-precipitation coating, 100 parts of hydroxy acrylic resin (solid content 50%): glass transition temperature of 110°C, mass average molecular weight of 150,000, solid hydroxyl value of 80 mgKOH / g, 22.5 parts of isocyanate curing agent (Desmodur L-75), NCO / OH of 1.05; adding 0.5 parts of microparticles (polyacrylate particles KE-P50), coating on both sides of a 50μm PET substrate layer 2 (KFDN-50SG5P) to form an anti-precipitation coating 1, with a single-side dry thickness of 0.5μm, to prepare a polyester film; testing after aging at 50°C for 24 hours.

[0050] Example 3 An anti-precipitation coating, 100 parts of hydroxy acrylic resin (solid content 50%): glass transition temperature of 80°C, mass average molecular weight of 20,000, solid hydroxyl value of 60 mgKOH / g, 23.7 parts of isocyanate curing agent (Desmodur N3390), NCO / OH of 1.2; coated on both sides of a 50μm PET substrate layer 2 (KFDN-50SG5P) to form an anti-precipitation coating 1, with a single-side dry thickness of 0.5μm, to obtain a polyester film; tested after aging at 50°C for 24 hours.

[0051] Example 4 An anti-precipitation coating, 100 parts of hydroxy acrylic resin (solid content 40%): glass transition temperature of 80°C, mass average molecular weight of 100,000, solid hydroxyl value of 76 mgKOH / g; 17 parts of isocyanate curing agent (Desmodur L-75), NCO / OH of 0.9, 1 part of microparticles (silicon dioxide particles MR-2G); coated on both sides of a 50μm PET substrate layer 2 (KFDN-50SG5P) to form an anti-precipitation coating 1, with a single-side dry thickness of 0.5μm, to obtain a polyester film; tested after aging at 50°C for 24 hours.

[0052] Example 5 An anti-precipitation coating, 100 parts of hydroxyl acrylic resin (solid content 40%): glass transition temperature of 80°C, mass average molecular weight of 100,000, solid hydroxyl value of 76 mgKOH / g; 5.4 parts of epoxy curing agent (TETRAD-X), epoxy group / hydroxyl ratio of 1.0; coated on both sides of a 50μm PET substrate layer 2 (KFDN-50SG5P) to form an anti-precipitation coating 1, with a single-side dry thickness of 0.5μm, to obtain a polyester film; tested after aging at 50°C for 24 hours.

[0053] Comparative Example 1 The test was conducted using 50 μm PET substrate layer 2 (KFDN-50SG5P).

[0054] Comparative Example 2 An anti-precipitation coating, 100 parts of hydroxy acrylic resin (solid content 40%): glass transition temperature of 80°C, mass average molecular weight of 100,000, solid hydroxyl value of 76 mgKOH / g; 10.2 parts of isocyanate curing agent (Desmodur L-75), NCO / OH of 0.6; coated on both sides of a 50μm PET substrate layer 2 (KFDN-50SG5P) to form an anti-precipitation coating 1, with a single-side dry thickness of 0.4μm, to obtain a polyester film; tested after aging at 50°C for 24 hours.

[0055] Comparative Example 3 An anti-precipitation coating, 100 parts of hydroxy acrylic resin (solid content 40%): glass transition temperature of 80°C, mass average molecular weight of 100,000, solid hydroxyl value of 76 mgKOH / g, 23.8 parts of isocyanate curing agent (Desmodur L-75), NCO / OH of 1.4; coated on both sides of a 50μm PET substrate layer 2 (KFDN-50SG5P) to form an anti-precipitation coating 1, with a single-side dry thickness of 0.4μm, to obtain a polyester film; tested after aging at 50°C for 24 hours.

[0056] Comparative Example 4 Polyurethane coating (BS CH271) was coated on both sides of a 50μm PET substrate layer 2 (KFDN-50SG5P) to form an anti-precipitation coating 1, which was then UV cured after drying. The dry thickness after single-side curing was 0.5μm, thereby obtaining a polyester film, which was tested.

[0057] Comparative Example 5 An anti-precipitation coating, 100 parts of hydroxy acrylic resin (solid content 40%): glass transition temperature of 50°C, mass average molecular weight of 18,000, solid hydroxyl value of 50 mgKOH / g, 23.8 parts of isocyanate curing agent (Desmodur L-75), NCO / OH of 0.7; coated on both sides of a 50μm PET substrate layer 2 (KFDN-50SG5P) to form an anti-precipitation coating 1, with a single-side dry thickness of 0.3μm, to obtain a polyester film; tested after aging at 50°C for 24 hours.

[0058] Comparative Example 6 An anti-precipitation coating, 100 parts of hydroxy acrylic resin (solid content 40%): glass transition temperature of 120°C, mass average molecular weight of 160,000, solid hydroxyl value of 130 mgKOH / g, 23.8 parts of isocyanate curing agent (Desmodur L-75), NCO / OH of 0.7; coated on both sides of a 50μm PET substrate layer 2 (KFDN-50SG5P) to form an anti-precipitation coating 1, with a single-side dry thickness of 0.6μm, to obtain a polyester film; tested after aging at 50°C for 24 hours.

[0059] The above embodiments and comparative examples were subjected to performance tests, and the methods for testing various physical properties are as follows: (1) Haze test: The haze was tested using a haze meter (model: NDH2000N) produced by Nippon Denshoku Industries Co., Ltd., with the reference standard being ASTM D 1003.

[0060] (2) High temperature test The sample was placed in a hot air circulation drying oven (model: KC-881) and the temperature was set to 150°C. After being placed for 4 hours, it was taken out and tested for haze after natural cooling. The surface was observed to see whether there was precipitation. No precipitation was marked as ○, a small amount of precipitation was marked as △, and a large amount of precipitation was marked as ×.

[0061] (3) High temperature and high humidity test The sample was placed in a KSON constant temperature and humidity testing machine (model: THS-C4T-100) at a temperature of 85°C and a humidity of 85%. After being placed for 72 hours, the sample was taken out and tested for haze after natural cooling. The surface was observed for precipitation. No precipitation was indicated as ○, a small amount of precipitation was indicated as △, and a large amount of precipitation was indicated as ×.

[0062] (4) Evaluation of bonding effect The PET coated with the anti-precipitation coating 1 on both sides was used, and an acrylic pressure-sensitive adhesive was coated on one side with a dry thickness of 10 μm. A release film 50 μm XD5QR was attached, and the film was aged at 50° C. for 72 hours. The die-cutting was performed, and the cut edge was observed with a magnifying glass.

[0063] When the acrylic pressure-sensitive adhesive, anti-precipitation coating 1 and PET are well combined, there is no powder loss or less powder loss during die-cutting; when there are problems in the combination of acrylic pressure-sensitive adhesive, anti-precipitation coating 1 and PET, the pressure-sensitive adhesive may fall off during die-cutting. Therefore, the die-cutting effect is used to evaluate the bonding effect of the pressure-sensitive adhesive. No powder loss or a small amount of powder loss can be considered to be a good bonding effect of the pressure-sensitive adhesive, and a large amount of powder loss can be considered to be a poor bonding effect of the pressure-sensitive adhesive. The die-cutting edge is evaluated as no powder ("○"), the presence of a small amount of powder is evaluated as ("△"), and the presence of a large amount of powder is evaluated as ("×").

[0064] The following table shows the test results of the above embodiments and comparative examples: According to the performance test results of the above embodiments and comparative examples, the anti-precipitation coating scheme of the present application is summarized as follows: 1. Haze test The haze test is an important indicator for evaluating the transparency and clarity of the coating. From the table data, the haze of Examples 1-5 is at a relatively low level (0.89-0.95), showing good transparency. The haze of Comparative Example 1 is significantly higher (15.06), indicating that the transparency of the coating is extremely poor; the haze of Comparative Examples 2 and 3 is relatively low, close to the performance of the examples; the haze value of Comparative Example 4 is 0.86, which is also good, but the die-cutting effect is slightly inferior to some examples.

[0065] Conclusion: The coating transparency of Examples 1-5 is significantly better than that of Comparative Example 1, and the difference with Comparative Examples 2 and 3 is small, showing good transparency.

[0066] 2. High temperature test The high temperature test simulates the stability of the coating in a high temperature environment. After 4 hours of testing at 150°C, no precipitation occurred in Examples 1-5, showing good stability ("○"). In contrast, a large amount of precipitation occurred in Comparative Example 1 ("×"), and a small amount of precipitation occurred in Comparative Examples 2, 5, and 6 ("△"). Comparative Examples 3-4 showed a smaller amount of precipitation, but still did not achieve the overall good effect of the embodiments.

[0067] Conclusion: The anti-precipitation performance of the embodiment is significantly better than that of the comparative example. Especially in a high temperature environment, the embodiment can better maintain the stability of the coating and avoid precipitation.

[0068] 3. High temperature and high humidity test The high temperature and high humidity test simulates the performance of the coating in an extreme hot and humid environment. Similar to the high temperature test, Examples 1-5 showed good anti-precipitation performance after 72 hours of testing at 85°C and 85% humidity, and the precipitation amount was "○" level, that is, no precipitation or very little precipitation. In contrast, Comparative Example 1 showed a small amount of precipitation ("△"), but the remaining comparative samples (Comparative Examples 2, 3, and 4) showed good or excellent anti-precipitation performance.

[0069] Conclusion: The anti-precipitation property of the embodiment is still excellent under high temperature and high humidity environment, which proves the reliability and stability of the coating in extreme environment.

[0070] 4. Die-cutting effect evaluation The die-cutting effect test is an evaluation of the bonding effect between the coating and downstream products (such as pressure-sensitive adhesives). The coatings of Examples 1, 2, and 4 were all ("○") in the evaluation after die-cutting, indicating that the coating was well bonded to the PET substrate and there was no problem of powder falling. Although Examples 3 and 5 also performed well ("△"), they were slightly inferior to the former. The die-cutting effects of Comparative Examples 3-6 were poor, especially Comparative Example 4, which had obvious powder falling ("×") during die-cutting, indicating that the coating was unstable in bonding to PET.

[0071] In summary, the anti-precipitation coatings of Examples 1, 2, and 4 have excellent stability under extreme environments such as high temperature and high humidity, and also have excellent performance in terms of transparency and bonding performance, and are suitable for application scenarios that require the coating to be resistant to environmental changes, have good transparency and strong bonding performance; The test results of Examples 1, 2, and 4 can reflect that the optimal material design of the anti-precipitation coating of the present application is: Hydroxylated acrylic resin: glass transition temperature is 60-110°C; solid hydroxyl value is 60-120 mgKOH / g; mass average molecular weight is between 20,000 and 150,000; The curing agent characteristics are as follows: Desmodur L-75 isocyanate type curing agent is preferred; The ratio of hydroxy acrylic resin to isocyanate curing agent is selected to be NCO / OH 0.7-1.05; Microparticles: The added amount is 0-10% of the solid content of hydroxy acrylic resin; The optimum thickness of the anti-precipitation coating formed after coating is 0.5 μm.

[0072] It can be seen that the anti-precipitation coating designed in this application not only has excellent resistance to environmental changes, but also can provide high transparency and strong adhesion performance, meeting the multiple requirements of high-end applications for coating performance. These technical advantages make this coating have broad application prospects in high-performance films, optical materials, electronic component protective layers and other fields.

[0073] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. An anti-precipitation coating, characterized in that: It comprises a hydroxy resin and a curing agent; the solid hydroxy value of the hydroxy resin is 60-120 mgKOH / g, the mass average molecular weight of the hydroxy resin is 20,000-150,000, and the glass transition temperature of the hydroxy resin is 60-110°C.

2. The anti-sedimentation coating according to claim 1, characterized in that: The hydroxy resin is a hydroxy acrylic resin.

3. The anti-sedimentation coating according to claim 2, characterized in that: The curing agent is an epoxy curing agent or an isocyanate curing agent.

4. The anti-sedimentation coating according to claim 3, characterized in that: The molar equivalent ratio NCO / OH of the isocyanate group of the isocyanate curing agent to the hydroxyl group of the hydroxy acrylic resin is 0.7-1.

2.

5. The anti-sedimentation coating according to claim 1, characterized in that: The anti-sedimentation coating further comprises microparticles, and the microparticles are selected from one or a combination of silicon dioxide particles, polyacrylate particles, and polystyrene particles.

6. The anti-sedimentation coating according to claim 5, characterized in that: The particle size D50 of the microparticles is between 0.1 μm and 1.5 μm.

7. The anti-sedimentation coating according to claim 5, characterized in that: The added amount of the microparticles is 0%-10% of the solid content of the hydroxy resin.

8. A polyester film, characterized in that: It comprises a substrate layer and an anti-precipitation coating arranged on at least one side of the substrate layer, wherein the anti-precipitation coating is obtained by curing the anti-precipitation coating according to any one of claims 1 to 7.

9. The polyester film according to claim 8, characterized in that: The thickness of the anti-precipitation coating is 0.3 μm-0.6 μm.

10. The polyester film according to claim 8, characterized in that: The polyester film has a film haze of less than 1.0%.

Citation Information

Patent Citations

  • Anti-precipitation PET (polyethylene terephthalate) optical film and application thereof

    CN107641454A

Cited By

  • Anti-precipitation coating and polyester film

    CN122278276A